Entrepreneurship and SME Development: Policy Considerations for Cambodia - Lee Keng Ng; Balbir Bhasin (International Journal of Small and Medium Enterprises and Business Sustainability, 2016)
As with most newly emerging economies, Cambodia needs to develop its small and medium sized enterprises (SMEs), which is the key engine for growth for all Southeast Asian developing countries. Though blessed with numerous natural resources, it is one of the poorest countries in Asia and its long-term economic development remains a daunting challenge. It is plagued by imminent poverty as a result of lack of opportunities to develop the human capabilities of the people to the fullest. Thus, the sense of entrenched stagnation in the wellbeing of the people is reflected in the extremely poor performance in the human development index (HDI). This paper evaluates the strategy and policy that needs to be in place for the country to succeed in private sector development with particular emphasis on creating the environment for stimulating economic activity particularly towards privatization and development of SMEs in order to be fully integrated into the ASEAN Economic Community (AEC).